Fiscal policy within a common currency area – growth implications in the light of neoclassical theory - Michał Konopczyński (Contemporary Economics)
We examine the long-run impact of fiscal policy on economic growth under the conditions of an economic and monetary union (EMU). The analysis is based on the neoclassical growth model of a small (in economic terms) open economy in an EMU. The core assumptions are perfect capital mobility, which results in identical interest rates across the EMU, and perfect mobility of goods, which leads to the convergence of price levels. The model is based on standard neoclassical assumptions, i.e., the output is determined by the Cobb-Douglas production function with a Harrod-neutral technical progress and constant returns to scale, capital and labor receive their marginal products, etc. We show that a unique long-run equilibrium exists and is characterized by the so-called natural rate of growth. The necessary and sufficient conditions of global asymptotic stability form a system of three non-trivial inequalities. We argue that in modern economies, these conditions are satisfied, except perhaps for very short periods of time. Furthermore, we show that the golden rules of fiscal policy have the form of an alternative optimal policy that crucially depends on the relation between the real interest rate and the natural rate of growth and on the relations between five other autonomous parameters.